Progressive collapse analysis of RC building frames with different seismic design levels - El-Shahat, Mohamed Foda (AUC Knowledge Fountain, 2013)
Progressive collapse prevention of buildings has recently become the focus of many researchers, design engineers, and officials all over the world particularly after the failure of the twin World Trade Center towers, New York City, USA in September 2001 and the increasing terrorist acts against governmental buildings. The progressive collapse is defined in the commentary of the American Society of Civil Engineers Standard 7-02 Minimum Design Loads for Buildings and Other Structures (ASCE 7-02) as “the spread of an initial local failure from element to element, eventually resulting in the collapse of an entire structure or a disproportionately large part of it". To date, there is no design code for blast resistant building design and progressive collapse prevention, but only design guideline sexist which are prepared by different bodies like Departments of defense (DoD) in USA as well as other countries and the General Service Administration (GSA) and the Federal Emergency Management Agency (FEMA). While design for progressive collapse prevention is possible at design stage, it becomes more challenging for already existing buildings. On the other hand, almost all recently designed and constructed buildings are designed for seismic resistance according to the seismic zone they are located in according to existing codes. Seismic design provisions allows for higher resistance to lateral reversible loads, and more ductility of structural frames and systems. Determining how much such provision adds to the building resistance to progressive collapse help when upgrading existing building for progressive collapse or when designing new ones. Furthermore, utilizing this seismic resistance and added ductility saves when designing for progressive collapse. This research focuses on identifying the effect of seismic design level on resisting progressive collapse. In this research the progressive collapse of three-story, multi-bay reinforced concrete structure is conducted. The procedure was conducted according to GSA and DoD guidelines. At first the building was designed according to Egyptian Code of Practice for design and construction of concrete structures (ECP203-2007). Three different levels of seismic design are considered by assuming that the building can be located in seismic zones 1, 3, and 5 according to the Egyptian Code for Calculating Loads and Forces on Structures and Buildings (201-2003). GSA guidelines and procedures are followed for progressive collapse analysis. All the three stages; gravity load, seismic load, and progressive collapse load analyses; are performed using commercially general purpose software computer program, SAP2000, that is available in the Construction lab, AUC. . Nonlinear static analysis was carried out where plastic hinges were allowed to form at designated locations of maximum moment. A total of 39 design and analysis case were considered and the results were analyzed to evaluate the effect of the different parameters on the building performance and its resistance to progressive collapse. The resistance to progressive collapse is measured by the number of formed plastic hinges and the resulting failed beams. The relationship between the seismic design levels, the slab thickness, number of formed plastic hinges and failed beams are presented graphically. The results showed that the vulnerability to progressive collapse becomes less as the seismic design level increased in higher seismic zone. This is mainly due to the increased member capacity, added ductility, and the seismic requirement for reinforcement details. It was also found that the slab membrane and bending actions contribute significantly in resisting progressive collapse and thus must be considered in the analysis.